Medical-social estimation and monitoring of foreign students health status studying in the Republic of Kazakhstan - Kharissova, N.M.; Abushakhmanova, A.H.; Krekesheva, T.I.; Mindubaeva, F.A. (Pub KSU, 2012)
The generalization of the personal experience of students in the development of a project to study the determinants of health and the impact of preventive measures in relation to the health of students-foreigners in KSMU at the departments of physiology; social medicine and organization of health care. Formation of a healthy way of life is a determining factor in the upbringing of the students of KSMU. In order to study the health status of students from India and Pakistan, a survey was conducted among the students of the first--the fifth year of medical faculty of KSMU. Students assessed the state of their health as excellent (38 %), average (57 %), poor (5%). For improvement of health status of students take a balanced diet (67 %), sports (33%).
Қазақстан Республикасында оқитын шетел студенттер денсаулығын медициналық-əлеуметтік тұрғыдан бағалау
Keywords: organism; еnvironment; diseases; health; development; deterioration; national safety; young generation; rehabilitation; physical exercises